Pavilon P brněnského výstaviště - vybrané části stavebně technologického projektu - Matuš, Ondřej (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Ve své diplomové práci řeším stavebně technologický projekt výstavby pavilonu P po technologické stránce. Cílem je vyřešení stavby z hlediska časových a finančních požadavků. Podrobněji se zabývám projektem zařízení staveniště, popisem provedení základových konstrukcí a stavebních ocelových konstrukcí.

I deal with the constructive technological project about building of pavilion P on the technology side in my masters thesis. The aim is to solve the structure from the aspect of time and financial requirements. I deal in more detail with the project of site equipment, with description the execution of foundation constructions and with construction steelwork.
PAVILON P OF THE BRNO FAIRGROUND - THE SELECTED PARTS OF THE BUILDING AND TECHNOLOGICAL PROJECT
Keywords: Pavilon; rozpočet; časový a finanční plán; ocelové konstrukce; piloty; bezpečnost práce; časový harmonogram; technologický předpis; kontrolně zkušební plán; zásady organizace výstavby; zařízení staveniště; Pavilion; budget; time and financial plan; steelwork; piles; safety work; a timetable; technological regulations; inspection and test plan; principles of organization of construction; site equipment